1990
DOI: 10.1016/s0735-1097(10)80354-7
|View full text |Cite
|
Sign up to set email alerts
|

Improved morphologic characterization of atrial septal aneurysm by transesophageal echocardiography: Relation to cerebrovascular events

Abstract: Transthoracic and transesophageal echocardiography was performed in 23 consecutive adult patients with an atrial septal aneurysm. In three patients with a cerebrovascular event the diagnosis was established by the transesophageal approach only. Interatrial shunting on transthoracic imaging with use of echocardiographic contrast imaging or Doppler color mapping, or both, was detected in 7 (41%) of 17 patients. On performing contrast imaging in combination with color flow mapping during transesophageal echocardi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
95
1
8

Year Published

1992
1992
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 202 publications
(111 citation statements)
references
References 38 publications
7
95
1
8
Order By: Relevance
“…1 The reported prevalence of ASA has also varied tremendously although the population-based TEE study reported a prevalence of 2.2%. 4 Up to 83% of patients with ASA also have a right-to-left shunt, 5 and in patients with PFO, the presence of an ASA has been associated with a larger separation between the septum primum and secundum, a prominent eustachian valve, presence of a Chiari network, and a larger right-to-left shunt. [6][7][8][9] Among patients younger than 55 years, as many as 40% of strokes are described as cryptogenic, with no identified cardioembolic or large vessel source, and in a distribution that is not consistent with small vessel disease.…”
Section: R E T I R E D R E T I R E Dmentioning
confidence: 99%
See 1 more Smart Citation
“…1 The reported prevalence of ASA has also varied tremendously although the population-based TEE study reported a prevalence of 2.2%. 4 Up to 83% of patients with ASA also have a right-to-left shunt, 5 and in patients with PFO, the presence of an ASA has been associated with a larger separation between the septum primum and secundum, a prominent eustachian valve, presence of a Chiari network, and a larger right-to-left shunt. [6][7][8][9] Among patients younger than 55 years, as many as 40% of strokes are described as cryptogenic, with no identified cardioembolic or large vessel source, and in a distribution that is not consistent with small vessel disease.…”
Section: R E T I R E D R E T I R E Dmentioning
confidence: 99%
“…While paradoxical embolism is the most commonly ascribed mechanism, there is some evidence to support alternative etiologies such as cardiac in situ thrombus formation and atrial arrhythmias. 5,14,16,[23][24][25] These alternative etiologies may have implications for management of these patients, as atrial arrhythmias are unlikely to resolve following closure procedures.…”
Section: R E T I R E D R E T I R E Dmentioning
confidence: 99%
“…3,4 A recent study based on TEE put its prevalence at 4.3% 5 and suggests that it is a more sensitive diagnostic tool than TTE. 5,6 Although 3D TEE clearly showed the aneurysm in this case, 2D TEE is sufficient to make a diagnosis of ASA. Several studies have classified ASA based on morphology and movement of the aneurysm.…”
Section: Discussionmentioning
confidence: 64%
“…5,9,10 Although not definitively proven, mechanism is presumed to be due to paradoxical interatrial shunting of thrombus since a high percentage of patients with ASA has PFO. 5,6 Presence of spontaneous echo contrast in the aneurismal cavity has been previously reported and thought to be a precursor to thrombus formation. 8 In a patient who presented for routine coronary artery bypass graft surgery, massive thrombus was noted within the aneurismal cavity that subsequently caused intraoperative embolic stroke.…”
Section: Discussionmentioning
confidence: 90%
“…None of them were associated with interatrial aneurysm which may lead to cerebral embolism, a cause of focal discrete neurological deficits (Schneider et al 1990). …”
Section: Discussionmentioning
confidence: 99%